Gender and Domestic Violence 2022
DOI: 10.1093/med-psych/9780197564028.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

Custody and Intervention Recommendations in Family Law Cases

Abstract: Children have been found to be adversely affected from not only having experienced physical abuse and neglect directly at the hands of their caregivers but also from having witnessed abuse between those caregivers, known as intimate partner violence (IPV). Because existing statutes limit child custody access to parents who have been shown to have engaged in such behavior, accusations are routinely brought forth by attorneys in family court cases on behalf of litigating parents. In this chapter, an overview is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Given research that has found such psychological impacts lead to adverse mental health outcomes, such as significant levels of depression, anxiety, and psychological distress, among other mental health issues (Hamel et al, 2015;Lawrence et al, 2009Lawrence et al, , 2012Taft et al, 2006), it is necessary to consider the outsize impact these abuse tactics have on victims. Such impacts are of particular importance given that psychological abuse and coercive control have led to their criminalization in the UK (Crown Prosecution Service, 2022), and though not considered criminal behavior in the U.S., though is being considered in custody decisions by attorneys, judges, and custody evaluators (Hamel & Baker, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given research that has found such psychological impacts lead to adverse mental health outcomes, such as significant levels of depression, anxiety, and psychological distress, among other mental health issues (Hamel et al, 2015;Lawrence et al, 2009Lawrence et al, , 2012Taft et al, 2006), it is necessary to consider the outsize impact these abuse tactics have on victims. Such impacts are of particular importance given that psychological abuse and coercive control have led to their criminalization in the UK (Crown Prosecution Service, 2022), and though not considered criminal behavior in the U.S., though is being considered in custody decisions by attorneys, judges, and custody evaluators (Hamel & Baker, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although psychological abuse/coercive control is not considered criminal behavior in the United States, it has been increasingly identified in family law codes, along with physical violence, as a factor in child custody decisions. Attorneys, judges, and custody evaluators have come to recognize psychological abuse as another form of IPA with deleterious consequences for adult victims as well children, both directly and indirectly, when a parent's parenting capabilities are diminished as a result, necessitating limitations on the custodial rights of the offending parent (Hamel & Baker, 2022). Unfortunately, because psychological abuse is a complex phenomenon, encompassing various types and degrees of abuse, it can be misunderstood (Follingstad, 2007) and its prevalence, and indeed its impact, can be exaggerated, deliberately or otherwise, by litigants seeking to gain custody of their children in the family court system (Hamel & Baker, 2022).…”
Section: Measuring Psychological Abusementioning
confidence: 99%
“…The implementation of IPV interventions is fundamental to reducing the victim/survivor's risk of suffering future violence. IPV perpetrator programmes were first developed over 40 years ago with the realisation that providing services to survivors of domestic violence and abuse without addressing the behaviour of perpetrators, was an inadequate response to this damaging violation of human rights (Hamel & Nicholls, 2006;Healey et al, 1999). Group treatment was favoured instead of individual therapy/counselling as it was believed that it offered abusers: more opportunities to expand their social networks to include others who are supportive of being nonabusive (Barner & Carney, 2011;Krishna et al, 2011;National Research Council et al, 1996); provided opportunities for peer learning (Yalom & Leszcz, 2020); and be potentially more cost effective by being able to cover a wide range of different treatment approaches (Karakurt et al, 2019).…”
Section: Palabras Clavementioning
confidence: 99%
“…It is suggested that such limitations in mind known also as gender paradigm, should be replaced (Rakovec-Felser, 2014). Some researchers (Hamel & Nicholls, 2007) suggest that only 1% -2% of men who are assaulted by their female partner report the abuse to the police, although the men can also be in distress suffered from violence.…”
Section: Introductionmentioning
confidence: 99%